Preparation and Characterization of Cetyl Trimethylammonium Intercalated Sericite - Hao Ding; Yuebo Wang; Yu Liang; Faxiang Qin (Advances in Materials Science and Engineering)
Intercalated sericite was prepared by intercalation of cetyl trimethylammonium bromide (CTAB) into activated sericite through ion exchange with the following two steps: the activation of sericite by thermal modification, acid activation and sodium modification; the ion exchange intercalation of CTA+ into activated sericite. Effects of reaction time, reaction temperature, CTAB quantity, kinds of medium, and aqueous pH on the intercalation of activated sericite were examined by X-ray diffraction (XRD) analysis, Fourier transform infrared (FT-IR) spectroscopy, differential scanning calorimetry (DSC), and thermogravimetric analysis (TGA). The results indicated that the CTA+ entered sericite interlayers and anchored in the aluminosilicate interlayers through strong electrostatic attraction. The arrangement of CTA+ in sericite interlayers was that alkyl chain of CTA+ mainly tilted at an angle about 60° (paraffin-type bilayer) and 38° (paraffin-type monolayer) with aluminosilicate layers. The largest interlayer space was enlarged from 0.9 nm to 5.2 nm. The intercalated sericite could be used as an excellent layer silicate to prepare clay-polymer nanocomposites.